Variations of collembolan communities in drained and diked salt marsh and adjacent farmland in coastal southeastern China - Gao, Meixiang; Liu, Yifei; Xiong, Lihu; Qi, Mengmeng; Li, Xin; Zheng, Ye; Liu, Jinwen; Xie, Zhijing; Yan, Xiujuan (Frontiers in Environmental Science, 2025)
Drained and diked salt marshes (DDSM) habitats, a typical form of coastal wetland, are undergoing ecological recovery, offering valuable insights into strategies for restoring and protecting biodiversity in reclaimed coastal wetlands. Richness, abundance, and composition of the collembolan community is expected to vary in response to changes in plant and soil in DDSM habitats and agricultural farmlands. However, knowledge on these variations remains limited. Therefore, we aimed to reveal the species richness, abundance, and composition of the collembolan community and the effect exerted by plant and soil variables in DDSM and agricultural farmlands. Soil samples were collected in coastal DDSM (northern enclosure and southern enclosure) and wheat farmland areas in Ningbo City, southeastern China, in April 2023. Species richness, rather than abundance, of the collembolan community, was significantly lower in DDSM habitats than in wheat farmlands. The collembolan community composition differed significantly between these two habitats. Ceratophysella skarzynskii Weiner (1996), Desoria sp12, Isotoma pinnata Fabricius (1781), and Sinella sp. were exclusively in DDSM habitats. Instead, the genera Arrhopalites, Heteraphorura, and Parisotoma preferred wheat farmlands. Plant coverage and height were important variables affecting collembolan community composition in DDSM habitats. DDSM habitats can sustain specific collembolan species, and their soil biodiversity warrants attention, particularly following rigorous reclamation measures. This study provides important information for restoring and protecting biodiversity in reclaimed coastal wetlands.